Interest of waiting time for spontaneous early reconnection after cavotricuspid isthmus ablation: A monocentric randomized trial. Issue 12 (22nd November 2017) - Marchandise, Sébastien; Scavée, Christophe; Barbraud, Cynthia; de Meester de Ravenstein, Christophe; Balola Bagalwa, Mittérand; Goesaert, Cédric; Reis‐Pinheiro, Ivone; le Polain de Waroux, Jean‐Benoit
Abstract: Introduction: The aim of this study was to determine the rate of recurrent atrial flutter (AFl) after isolated cavotricuspid isthmus (CTI) ablation and to evaluate the impact of a waiting period with the search for early resumption of the CTI block on the long‐term outcome. Method: Three hundred and nineteen consecutive patients referred for typical AFl ablation were randomly assigned to CTI ablation with continuous reevaluation of the CTI block during 30 minutes and early reablation if needed (waiting time [WT] + group, n  =  155) or to CTI ablation with no waiting period after proven bidirectional CTI block (WT − group, n  =  164). All patients were regularly followed‐up. Result: In the WT+ group, 10 patients (6%) presented a recovery across the CTI (time to recovery: 17 ± 7′) and were reablated at the end of the waiting period. After a median follow‐up of 21 months, the rate of recurrent AFl was significantly higher in the WT − group as compared to the WT+ group (11.6% [19/164] vs 2.5% [4/155], respectively; P  =  0.007). However, no significant differences in the subsequent rate of AF were observed between the two groups (29% [WT −] vs 32% [WT+], P  =  0.66). During the follow‐up, 28 patients from the WT − group underwent a second ablation procedure (16 AFl redo and 12 AF ablation) versus 10 patients form the WT+ group (three AFl redo and seven AF ablation). Conclusion: Waiting 30 minutes after CTI ablation to check for early resumption and early reablation allows for decreasing significantly the rate of recurrent atrial flutter.